Singapore mathematics approach in aiding the modular print distance learning modality in teaching mathematics - Bacus, Mark Ryan J.; Guillena, Junge B. (SAINTIS Publishing, 2023)
A research investigation was conducted to find out the efficacy of the Singapore mathematics approach in aiding the modular print distance learning modality. This study was a quasi-experimental research design using two groups of participants, the Singapore math group and the traditional group. The group was fairly the same with both groups having the same number of participants and the grades of the students were fairly equal. Each group consisted of 42 participants, for a total of 84 participants. The participants were given a pretest to measure their prior knowledge. The result showed that the Singapore Math learning approaches positively affected the learning of the learners in mathematics. In addition, the use of the Singapore Mathematics approach was significantly better than the traditional approach in teaching solving word problems among the learners it has a significant improvement in the knowledge and application skills of the learners was clearly manifested in the Singapore Math approach compared to the Traditional approach of teaching. Further, the use of the Singapore Mathematics Approach was significantly better than the Traditional Approach in teaching solving word problems among the learners. Hence, the use of the Singapore Math Approach should be encouraged as an alternative to teaching solving word problems inside the classroom.